2015
DOI: 10.1186/s12966-015-0234-0
|View full text |Cite
|
Sign up to set email alerts
|

The creation of a healthy eating motivation score and its association with food choice and physical activity in a cross sectional sample of Irish adults

Abstract: BackgroundThis study aimed to develop a healthy eating motivation score and to determine if dietary, lifestyle and activity behaviours vary across levels of motivation to eat a healthy diet with a view to informing health promotion interventions.MethodsA cross-sectional survey of food intake, physical activity, lifestyles and food choice attitudes was conducted in a nationally representative sample of 1262 adults in the Republic of Ireland aged 18 years and over.ResultsIncreasing score for health motivation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
52
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 57 publications
(55 reference statements)
8
52
4
Order By: Relevance
“…We based the restaurant design and menu information (including meal choices, energy content, price) on a popular UK fast-food restaurant and participants reported that the food items in the virtual environment were common in fast-food restaurants, and that there were food items they would have normally ordered in the real world. We also found evidence that participants' food choices in the virtual environment were similar to what would be expected in everyday life, e.g., as shown in other research [30,66], participants tended to order less energy overall if they reported being motivated by health when making everyday food choices. Although other research has shown that food choice tasks using virtual environments are valid [67,68], participants did not spend their own money and did not have to consume what they ordered.…”
Section: Discussionsupporting
confidence: 81%
“…We based the restaurant design and menu information (including meal choices, energy content, price) on a popular UK fast-food restaurant and participants reported that the food items in the virtual environment were common in fast-food restaurants, and that there were food items they would have normally ordered in the real world. We also found evidence that participants' food choices in the virtual environment were similar to what would be expected in everyday life, e.g., as shown in other research [30,66], participants tended to order less energy overall if they reported being motivated by health when making everyday food choices. Although other research has shown that food choice tasks using virtual environments are valid [67,68], participants did not spend their own money and did not have to consume what they ordered.…”
Section: Discussionsupporting
confidence: 81%
“…Of special interest is the association between health concerns in terms of diet and actual eating behavior, as it seems intuitive that stronger healthy eating motivation (HEM) leads to choosing health-promoting foods. This assumption is supported by findings from previous studies that have identified HEM as a factor for higher intake of fruits and vegetables and lower consumption of energy-dense foods [2][3][4][5].…”
Section: Introductionsupporting
confidence: 77%
“…Physical activity plays an important role in some aspects of food choices and it has been 356 associated with a better diet quality and higher intake of fruits and vegetables (Bellisle, 1999; King, 357 1998; Naughton et al, 2015). However, in this study the scores for all levels of physical activity 358…”
Section: ) 306 307 Social and Professional Factors 308mentioning
confidence: 72%